Heart re-transplantation in Eurotransplant - Smits, Jacqueline Mathilde Albertine; Pauw, Michel De; Schulz, Uwe; Cleemput, Johan Van; Raake, Philip; Knezevic, Ivan; Caliskan, Kadir; Sutlic, Zeljko; Knosalla, Christoph; Schoenrath, Felix; Szabolcs, Zoltan; Gottlieb, Jens; et al. (Transplant international, 2018)
Internationally 3% of the donor hearts are distributed to re-transplant patients. In Eurotransplant, only patients with a primary graft dysfunction (PGD) within 1 week after heart transplantation (HTX) are indicated for high urgency listing. The aim of this study is to provide evidence for the discussion on whether these patients should still be allocated with priority. All consecutive HTX performed in the period 1981-2015 were included. Multivariate Cox’ model was built including: donor and recipient age and gender, ischaemia time, recipient diagnose, urgency status and era. The study population included 18 490 HTX, of these 463 (2.6%) were repeat transplants. The major indications for re-HTX were cardiac allograft vasculopathy (CAV) (50%), PGD (26%) and acute rejection (21%). In a multivariate model, compared with first HTX hazards ratio and 95% confidence interval for repeat HTX were 2.27 (1.83-2.82) for PGD, 2.24 (1.76-2.85) for acute rejection and 1.22 (1.00-1.48) for CAV (P < 0.0001). Outcome after cardiac re-HTX strongly depends on the indication for re-HTX with acceptable outcomes for CAV. In contrast, just 47.5% of all hearts transplanted in patients who were re-transplanted for PGD still functioned at 1-month post-transplant. Alternative options like VA-ECMO should be first offered before opting for acute re-transplantation.